Aspectos da biologia reprodutiva de Eretmochelys imbricata (testudines, cheloniidae) no litoral sul do Rio Grande do Norte, Brasil - Santos, Armando José Barsante (2008)
Female hawksbill turtles (Eretmochelys imbricata) nesting along the southeastcoastline of Rio Grande do Norte State, Brazil (6º13'40"S, 35º03'05"W) were captured and weighed during the four months from January to April 2007, in the course of the annual egglaying season, which extended from 06 rd November 2006 to 30 rd May 2007. In all, 99 weight measurements were performed. On first contact the females exhibited an average post-oviposition weight of 79.1 kg (range 56.2-98.9 kg, SD = 10.9 kg, n = 44 females). Those individuals which were subsequently recaptured showed a mean weight loss of 1.7 kg (range 0.7-4.5 kg, SD = 1.0 kg, n = 39 sets of measurements on 20 females) in the interval between two consecutive post-ovipositions, separated by a maximum time interval of 17 days. In the cases where the female aborted the nesting process, the pre-oviposition weight was measured. The clutch weight, that is to say, the weight loss between consecutive pre-oviposition and post-oviposition measurements (separated by a maximum time interval of 3 days), was found to be 5.2 kg (range 4.3-6.0 kg, SD = 0.9 kg, n = 6 sets of measurements). This value is significantly higher (t-test, p<0.001) than the loss between two consecutive post-oviposition measurements with the same female. The mean recovery in body weight, that is to say, the average gain in weight between successive post-oviposition and pre-oviposition captures of the same individual (separated by a time interval of 12 to 17 days), was found to be 3.0 kg (range 1.9-4.3 kg, SD = 1.0 kg, n = 4 sets of measurements) Although the small sample size makes it unwise to generalise, the recovery in body weight was found to be always significantly lower (t-test, p<0.005) than the clutch weight. This fact is in agreement with the observed weight loss tendency throughout the breeding season for this species. Considering the clutch weight and the internidal recovery in body weight we found that the total weight loss of the adult hawksbill females after three to five nesting events varied from 10.4% (range 8.7-11.9%, SD = 1.6%, n = 3) to 14.1% (range 11.8-15.4%, SD = 1.3%, n = 6) in relation to their initial pre-oviposition weight. If there were no body weight recovery during the internesting interval we estimate that a female that nests three to five times in the course of the season would lose from 19% to 31% of its initial weight. We emphasise that our clutch weight estimate was performed by weighing the females and not by multiplying the number of eggs in the nest by their average unit weight. In this way, our measurements take into account the loss of liquid during the oviposition. Despite the unequivocal evidence of body weight recovery during the internidal interval, it is not clear if the cause of this process is rehydration or feeding